Tinjauan Aspek Kepemimpinan dan Manfaat Pertempuran Laut Karang Tahun 1942 Bagi TNI Angkatan Laut - Haryanto Wibowo (Mahesa Research Center, 2022)
This article aims to analyze the leadership aspect in a case study of the 1942 Battle of the Coral Sea between the Allied Navy and the Imperial Japanese Navy. The focus of this article is on the leaders of the two sides in leading the Coral Sea battle. To approach this problem, the theoretical reference of situational, transformational, and military leadership styles is used which is the basis for analyzing aspects of leadership. The data were collected based on literature studies of books, and journals related to the Coral Sea battle in terms of leadership and analyzed qualitatively. This study concludes that the Japanese side has a leader who has experience and leadership who has a transformational concept, namely Admiral Yamamoto. In addition, Rear Admiral Fletcher's breakthrough concept of the Allied fighting strategy was part of a transformational leadership style, one aspect of which was to go beyond self-interest by prioritizing organization. The leadership style, whether situational, transformational, or military, can be applied to all ranks of Indonesian Navy soldiers in carrying out daily tasks and carrying out operational tasks in the area of operation.